1981
DOI: 10.1007/bf00410690
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interferon in therapy of skin and head and neck tumors

Abstract: The clinical experimental model of HLI application in the therapy of skin and mucosal cancers of the head and neck has opened new prospects in HLI utilization. Based on clinical observations and research it may be concluded that HLI, if applied topically in the area of the tumor, may induce its disappearance or regression. If applied presurgically, it blocks the dispersion of neocytes during surgery. Also, HLI inhibits metastatic dissemination of malignant tumors and therefore might reduce the percentage of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1985
1985
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…It appears that the intratumoral route of administration may have the greatest direct antitumor effect (21). On the other hand, it has been shown that HLIFN, given IM or IV, initiates a multi¬ tude of immunomodulatory effects that may add to the antitumor response (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…It appears that the intratumoral route of administration may have the greatest direct antitumor effect (21). On the other hand, it has been shown that HLIFN, given IM or IV, initiates a multi¬ tude of immunomodulatory effects that may add to the antitumor response (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…Responses for other common solid tumors such as bronchogenic carcinoma (33,34) and colon cancer (35,36) have been negative. Preliminary trials with crude alpha interferon preparations from Yugoslavia suggested some activity for head and neck cancers (37,38); however, these results have not been confirmed in the United States.…”
Section: Solid Tumorsmentioning
confidence: 70%
“…IFN-β in nasopharyngeal cancer is the only indication that was established successfully [21]. Local administrations of interferons to the tumor were only casually reported over the years [22].…”
Section: Biological Modifiers In the Treatment Of Head And Neck Cancermentioning
confidence: 99%